Limited Genetic Connectivity Among Sargassum horneri (Phaeophyceae) Populations in the Chinese Marginal Seas Despite Their high Dispersal Capacity - Li, Jing-Jing (Journal of phycology, 2020)
© 2020 Phycological Society of America.